2014
DOI: 10.4102/sajems.v17i5.638
|View full text |Cite
|
Sign up to set email alerts
|

Ethical business practices in the Eastern Cape automotive industry

Abstract: High profile scandals have brought about a renewed interest in business ethics and, in particular, inunderstanding the factors that promote ethical behaviour. Business ethics is about identifying andimplementing values, rules and standards of conduct for guiding morally right behaviour in an organisation’sinteraction with its stakeholders. Against this background a quantitative analysis of the ethical practices of46 companies operating in the Eastern Cape automotive industry was conducted to determine the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Less than two-thirds of respondents indicated that their organisations had ethics training in place, which is significantly less than the 81 percent of US companies that provide ethics training (ERC, 2014). Lloyd et al (2014) found that 85 per cent of South African organisations have a person who is responsible for ethics and, according to the SACEI (Groenewald & Geerts, 2013), employees" awareness of this initiative had increased significantly from 2009 to 2013. The Ethics Institute (Groenewald, 2016) report, however, that awareness of safereporting mechanisms (an ethics hotline, 79%) and ethics officers or persons responsible for ethics management and advising on ethical matters (58%) declined substantially from 2013 (83% and 72% respectively) to 2016.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Less than two-thirds of respondents indicated that their organisations had ethics training in place, which is significantly less than the 81 percent of US companies that provide ethics training (ERC, 2014). Lloyd et al (2014) found that 85 per cent of South African organisations have a person who is responsible for ethics and, according to the SACEI (Groenewald & Geerts, 2013), employees" awareness of this initiative had increased significantly from 2009 to 2013. The Ethics Institute (Groenewald, 2016) report, however, that awareness of safereporting mechanisms (an ethics hotline, 79%) and ethics officers or persons responsible for ethics management and advising on ethical matters (58%) declined substantially from 2013 (83% and 72% respectively) to 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand and prevent unethical behaviour in the workplace, it is essential to take cognisance of contextual, organisational and individual drivers of such behaviour. Contextual drivers include, for example, the competitiveness of the business environment (Kulik, O"Fallon & Salimath, 2008) and religiosity or national culture (Rashid & Ibrahim, 2008;Holmquist, 2013), while intra-organisational factors that have been reported as antecedents of unethical behaviour include a lack of ethical leadership (Lloyd et al, 2014;Mayer, Nurmohamed, Treviño, Shapiro & Schminke, 2013), organisational culture (Ardichvili, Jondle & Kowske, 2010;Clarke, 2011), ethical climate (Bartels, Harrick, Martell & Strickland, 1998) and the absence of or disregard for a code of ethical conduct (Kish-Gephart, Harrison & Treviño, 2010). Individual-level factors such as morality (Klikauer, 2012) or moral ideology (Ruiz-Palomino & Martinez-Cañas, 2011) an individual"s propensity for moral disengagement (Moore et al, 2012) and, to a limited extent, demographic characteristics such as age, gender, education level and marital status (Yücel & Çiftci, 2012;Kish-Gephart et al, 2010) may also impact on an individual"s propensity to engage in unethical behaviour.…”
Section: Ethics In the Workplacementioning
confidence: 99%
See 3 more Smart Citations